A Large Retrospective Series of Pregnancy and Delivery After Midurethral Sling for Stress Urinary Incontinence. Issue 5 (September 2016) - Adams-Piper, Emily; Buono, Kristen; Whitcomb, Emily; Mallipeddi, Padma; Castillo, Peter; Guaderrama, Noelani
Abstract : Objectives: The aim of this study was to review the complete medical course, including safety, efficacy, and medical decision making, of patients who delivered a pregnancy after the placement of midurethral sling (MUS) within a large health maintenance organization. Methods: We conducted a retrospective case series of patients within the Northern and Southern California Permanente Medical Group who were identified based on procedural codes for placement of MUS for stress urinary incontinence. Electronic medical records with MUS code were referenced against records of live births within the health care system. Demographic and clinical data were abstracted through extensive, standardized physician review of the electronic medical records of all identified patients. Results: Twenty-six patients were identified and included in analysis. Sixteen patients had a retropubic MUS, and 10 had a transobturator MUS. Twenty-one of 26 patients reported subjective resolution of urinary incontinence after MUS. Fourteen of the 25 first deliveries after MUS were cesarean section (CS). Of these, 5 CS were elective primary for the indication of previous MUS, 5 were elective repeat CS, and the remaining 4 were for fetal indications. Eleven patients had spontaneous vaginal deliveries. There were no MUS-related pregnancy complications. One patient developed recurrent stress urinary incontinence postpartum, for which she underwent repeat MUS within a year resulting in cure of incontinence. Conclusions: This case series corroborates previous series demonstrating the safety and durability of MUS after subsequent pregnancy. Abstract : This large case series demonstrates that the majority of women who deliver following the placement of a midurethral sling maintain continence regardless of the route of delivery.